Akutna ishemična možganska kap, povezana z okužbo z novim koronavirusom - Čatlak, Katarina (Rehabilitacija (Ljubljana), 2021)
Evidence from SARS-CoV-2 studies indicate that the new coronavirus also affects the central nervous system. A retrospective study from Wuhan, China, reports ischemic stroke as one of the more severe complications associated with the coronavirus infection. In 2020, ischemic stroke occurred in 8 out of 352 patients admitted to our hospital due to a SARS-CoV-2 infection. The paper presents the case of an 82-year-old patient with previously diagnosed atrial fibrillation on apixaban therapy who suffered her first ischemic stroke most likely associated with the coronavirus infection. Early guidelines on the treatment of patients hospitalized with COVID-19 did not include physical therapy, regarding it as not essential. However, our early observations show that physical therapy is an important part of the acute treatment of coronavirus patients. Having suffered an ischemic stroke associated with the coronavirus infection, the patient achieved important progress in motor functions thanks to physical therapy. Our conclusion is that with some necessary modifications, therapy may be useful and is required. The paper describes the adjustments made to physical therapy work due to contact isolation protocols, and the problems observed during such work.
Keywords: COVID-19; early rehabilitation; fizioterapija; infection; ischemic stroke; ishemična možganska kap; okužba; physical therapy; Rehabilitation; zgodnja rehabilitacija